Hasil Belajar Akuntansi Ditinjau Dari Persepsi Siswa Mengenai Keterampilan Guru dalam Mengajar dan Disiplin Belajar Pada Siswa Kelas X Di SMK Prawira Marta kartasura tahun ajaran 2015/2016 - Setyowati, Rohma Dwi, Dra. Titik Asmawati, SE, M.Si (2016)
The purpose of this research are: 1) The effect of students' perceptions about the skills of teachers in teaching the learning outcomes of accounting 2) The effect of the discipline of learning to the learning outcomes of accounting. 3) The influence of students 'perceptions regarding teachers' skills in teaching and discipline of learning on learning outcomes accounting. This including quantitative descriptive research type with drawing conclusions through statistical methods. The population in this study were all students of class X SMK Prawira Marta Kartasura the academic year 2015/2016. samples taken as many as are 75 students with Proportional Random Sampling in a way the draw. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 18.444 + 0.699 X1 + 0.346 X2. The equation shows that the learning outcomes are influenced by perceptions of Accounting students about teachers' skills in teaching and learning discipline. The conclusions drawn are: 1) Students' perceptions about the skills of teachers in teaching the learning outcomes acceptable accounting. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 8.456> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 74% and the effective contribution of 45.4%. 2) Discipline learning on learning outcomes acceptable accounting. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 4.381> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 26% and the effective contribution of 15.9%. 3) Perceptions of students on teachers' skills in teaching and discipline of learning to the learning outcomes acceptable accounting. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 56.939> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.613 indicates that the influence of students 'perceptions regarding teachers' skills in teaching and discipline of learning to the learning outcomes of accounting amounted to 61.3%, while the rest influenced by other variables.